Design and Development of a Control System for Nanofiber Electrospinning - Dayat Kurniawan; Purwoko Adhi; Muhammad Nasir (National Research and Innovation Agency, 2013)
This paper describes the development of a control hardware and software for a nano-fiber electro-spinning system. The hardware consists of motor driver boards, a high DC voltage board, and a main control board. The user interface software on PC is developed using Visual Studio C # 2010 express edition. The motor driver boards are controlled by an ATmega8 microcontroller IC, while the main board is controlled by an ATmega 128 microcontroller IC. Communication between the main board and the motor driver boards uses the inter integrated circuit (I2C), while communication between PC and the main board uses a serial communication at a baud rate of 9,600 bps. The high DC voltage generator is designed to have an output of 0-25 kV. High DC voltage output is configurable by giving a combination of low logic and high impedance into a six bit input. The result show that maximum output of high DC voltage is 25.025 kV with formula of curve is y = 1x – 0.0244 with R2 = 0.9998 and PC software interface can work very well. Polymer flow rate can be configured from PC interface software via I2C connected to the main board. The flow rate y follows the RPM setting x, according to the formula y = 0.954x – 0.0099 with R2 = 1. The results of scanning electron microscope (SEM) for morphology analysis of PVDF copolymer composite nano-fiber shows that the average diameter of the resulted fiber is 136.43 nm, when output high DC voltage is set to 15 kV and speed of syringe pump is set to 5 RPM.